SINTESA NANO ZIRKON DARI PASIR ZIRKON LOKAL DENGAN METODE FUSI KAUSTIK SODA-PRESIPITASI-KALSINASI - Alvika Meta Sari; Efrizon Umar; Djoko Hadi Prajitno; Rian Fitriana; Anwar Ilmar Ramadhan; Firmansyah Firmansyah; Istianto Budhi Rahardja; Akmal Imam Faisal; Fikriyansyah Fikriyansyah (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
Indonesia is one of countries that has the potential of mineral natural resources in the form of zircon sand. Zircon sand is a raw material that has the potential to be synthesized into nano zircon because of its ingredients of zircon oxide (ZrO2). In this study the aim was to study the aim to synthesize nano zircon from local zircon sand from Kalimantan using caustic soda-precipitation-calcination modification method. Nano zircon was prepared in this study by modifying existing methods, namely caustic fusion, washing, acid leaching using hydrochloric acid, precipitation using ammonia and calcination processes to produce nano zircon in the form of white powder. The efficiency of the process was analyzed by calculating the yield of the product formed, then the FTIR (Fourier Transform Infra-Red) spectroscopic test was performed to determine the functional groups of nano zircons and the morphology was analyzed using SEM (Scanning Electron Microscopy). Yield obtained is 2.7%Â with the size of nano zircon is 41.983 nm. The FTIR spectrum shows the presence of the-Zr-O2 functional group at wave numbers 600 â€“ 700 cm-1.